The Influence of the Leadership of the Head of UPTD Pendidikan on the Performance of the Principals of Public Elementary Schools in Pakkat District, Humbang Hasundutan Regency - Suparmo AH Simamora; Hotlin Siregar (Institute of Computer Science (IOCS), 2021)
Education is an aspect that cannot be separated from all aspects of human life, both education in the macro sense and education in the micro sense, because each individual experiences an educational process. This study aims to analyze how the influence of the leadership of the Head of UPTD Pendidikan on the performance of the Principals of Public Elementary Schools in Pakkat District, Humbang Hasundutan Regency. The data analysis method used is simple analysis method, simple linear regression analysis and t test. The sample in this study was all the Principals of Public Elementary Schools in Pakkat District, Humbang Hasundutan Regency, as many as 34 people. The data obtained from the questionnaire taken from a sample of 34 people can be obtained with the result that rcount (0.920)> rtabel (0.349) reveals that there is a significant relationship between the Leadership of the Head of UPTD Pendidikan (X) and the Performance of the Principal of Primary Schools (Y) Se - Pakkat District, Humbang Hasundutan Regency. Based on table 3.2 Guidelines for Interpretation of Correlation Coefficients, the coefficient found is 0.920, including the very strong category. So there is a very strong relationship between the Leadership of the Head of UPTD Pendidikan (X) and the Performance of the Principals of Elementary Schools (Y) in Pakkat District, Humbang Hasundutan Regency. R Square of 0.846 or 84.60%. This shows that the influence of the leadership of the Head of UPTD Pendidikan (X) with the Performance of the Principals of Elementary Schools (Y) in Pakkat District, Humbang Hasundutan Regency is 84.60% and the rest is 15.40% based on other factors not discussed in this study. . The regression of the Equation is Y = 3,915 + 0,569X. The regression equation can state that if the Head of the UPTD Pendidikan or X = 0 then the Principal Performance value or Y will increase by 3,915. The significance of the variables is 13,235. Then the value is compared with t table with an error level of 5% df = n-2 = 32. The value of t table is 2.042. In accordance with the requirements of the hypothesis which states that count (13,235)> table (2,042) can reject that the Leadership of the Head of UPTD Education (X) has a positive and significant effect on the Performance of Primary School Principals (Y) in Pakkat District, Humbang Hasundutan Regency, the research hypothesis received.